Possible Protective Effects of Omega 3, Diazepam and their Combination Against Yohimbine-Induced Clonic Seizure in Mice: Comparative Study - Ibrahim, Manal Abdulkhaliq; Khudhair, Alaa Radhi; AL-shawi, Nada Najia (Iraqi Journal of Pharmaceutical Sciences, 2021)
Yohimbine is actually confirmed in the United States to be utilized for erectile dysfunction; and recently such drug has become commonly used in body-building communities for its presumed lipolytic and sympathomimetic effects. But ingestion of such drug can bring about epileptic neurotoxic effects. Many antiepileptic drugs can be utilized to counteract myoclonic seizure; furthermore, diazepam can be used to oppose such type of seizure; in addition, surrogate therapeutic options such as omega 3 may also be utilized. In this study, twenty-four (24) mice of both sexes weighing 20-25g were randomly-allocated into 4 groups (6 animals each group) as follows: Group I- Yohimbine-induced clonic seizure [mice orally-administered DMSO (10%), and after 30 min, animals Sc. injected with 45mg/kg yohimbine). Group II- Diazepam-treated as standard drug: It is Sc. injected at a dose of 2mg/kg, and after 30 minutes, yohimbine at a dose of 45mg/kg is Sc. injected. Group III- Omega 3 (40 mg/kg) is orally-administered, and after 30 min 45mg/kg yohimbine is Sc. injected. Group IV- Combination of omega 3 (40mg/kg) is orally-administered then and after ten minutes, diazepam was IP injected 2mg/kg then after 20 minute, 45mg/kg yohimbine is Sc. Injected. The result of this study showed that omega 3 has non-optimal antiepileptic effect; where, it is un-able to reduce the onset and frequency of epilepsy tone in mice during several time periods (30-120min); and data weren’t significantly different when compared to diazepam. But omega 3 reduced onset of epilepsy in combination with diazepam when compared with diazepam alone. As well as omega 3 caused small percent changes frequency of epilepsy tone through 120 min when compared with other groups. Conclusion: Omega 3 fatty acid had partial beneficial effect; where, alone it has a role for decreasing onset of epilepsy; but, its combination with diazepam had significant role for reducing onset of epilepsy against yohimbine-induced seizure model. Additionally, omega 3 alone and in combination with diazepam have negligible role for reduction frequency of epilepsy.